Corruption in Iraq after 2003 and its repercussions on national sovereignty: international and political journal - Kadum, Lecturer Dr. Ali Mahdi (The International and Political Journal, 2025)
After 2003, Iraq witnessed a period of oversight and oversight by oversight and administration. Public workers, the absence of targeted groups, and the prevalence of party and partisan favoritism led to a fertile environment for the growth of networks, primarily within the state. This creativity manifested itself in various forms, including the waste of public funds, fictitious contracts, and the politicization of employment, in addition to the penetration of joint influence within various political and administrative parties. This does not only mean the lack of internal oversight, but also direct investment in national sovereignty, as it contributed to the emergence of the state and the collapse of confidence in governing institutions. This led to an interest in intervening in Iraqi affairs and the ability to lead nationally through networks of political and economic influence. On the other hand, it contributed to achieving economic development,